Integrating Rebana-Based Local Wisdom into Physics Learning: Analyzing Students’ Science Literacy by Region - Nasution, Nabila Nur Almaida; Santoso, Irsyad Yusuf; Habibi, H; Suprapto, Nadi; Hidaayatullaah, Hasan Nuurul; Putri, Pretty Oktianti Menur Kusuma (Studies in Philosophy of Science and Education, 2024)
This study aims to analyze the level of scientific literacy among students from various regions, including regions that are not generally recognized as religious cities, by incorporating the context of local wisdom of the rebana musical instrument into the physics literacy instrument. This study uses a quantitative descriptive approach to measure and compare the level of physics literacy of students based on region. The results of the study indicate that scientific literacy is not only influenced by the religious background of a region but also by the relevance of the learning model, exposure to local culture, and the alignment between learning materials and students' life experiences. These findings emphasize the importance of integrating local and cultural contexts in physics learning to create meaningful learning experiences and encourage deeper understanding of concepts.